Helium Rydberg Atoms in a Strong Magnetic Field: A Classical View on Atomic Physics - Karremans, Kees (Science Diliman: A Journal of Pure and Applied Sciences; Vol 13 No 2 (2001), 2012)
The hydrogen atom in a strong, uniform magnetic field, is a quantum-mechanical system with chaotic dynamics in the semi-classical limit. Classically irregular motion arises when the spherical Coulomb term in the Hamiltonian becomes of the same order of magnitude as the cylindrical diamagnetic term. For a hydrogen atom in the ground state, a magnetic field of more than 10^5 T is required to create this situation. Rydberg atoms (atoms with a high principal quantum number n>20) allow us to investigate this system at field strength that can be generated in a laboratory setup. The scaling properties of Rydberg atoms in external fields can be used to perform experiments under fixed classical conditions. These scaling transformations show that the dynamics of the system depends on single parameter, the scaled energy ε. In scaled-energy experiments, the field strength is adapted to the laser frequency in order to keep this scaled energy ε = EB^-2/3 constant.